DOES ENTREPRENEURSHIP EDUCATION MATTER FOR ISLAMIC HIGHER EDUCATION STUDENTS"™ ENTREPRENEURIAL READINESS? - Cahyani, Utari Evy; Masruri, Siswanto; Hanafi, Syafiq Mahmadah (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
This research examines the empirical linkages among entrepreneurship education, entrepreneurial mindset, entrepreneurial skill, and entrepreneurial readiness of Islamic higher education students in Indonesia. This research also highlights the intervening role of an entrepreneurial mindset and entrepreneurial skills in the linkages between entrepreneurship education and entrepreneurial readiness. This study is based on social cognitive theory. The article is a quantitative research using a survey method. Data were collected using an online questionnaire with a sample of 310 Islamic college students in Indonesia. The data were analyzed using PLS-SEM to identify hypotheses. The results indicate that entrepreneurship education improves the entrepreneurial mindset and entrepreneurial skills. Surprisingly, entrepreneurship education has no direct effect on entrepreneurial readiness. Although entrepreneurship education indirectly affects entrepreneurial readiness, intervened by an entrepreneurial mindset and entrepreneurship skills. The results showed that the entrepreneurial mindset and entrepreneurship skills determine entrepreneurial readiness. The findings of this study are essential for Islamic higher education to provide entrepreneurship education that aims to develop an entrepreneurial mindset and improve entrepreneurship skills.